THE EFFECT OF USING PICTORIAL POSTER ON STUDENT ABILITY IN WRITING DESCRIPTIVE TEXT IN VIII CLASS OF SMP NEGERI 4 BADAR IN ACADEMIC YEAR 2021/2022 - Shinta Shinta; RAJA FAUZIAH; Muhammad Tahir (STKIP USMAN SAFRI KUTACANE, 2023)
This study deals with the effect of using pictorial poster on student ability in writing descriptive text in viii class of SMP Negeri 4 Badar Academic Year 2021/2022. Its objective is How The Effect to descriptive text of grade VIII at SMP Negeri 1 Ketambe using Pictoral Poster effective?. The population on the research is the students of SMP Negeri 4. The sample that used is 1 class total 30 student. The research design is a research using Quantitative research methods using a descriptive approach. A descriptive approach is used to collect data systematically, factually, and quickly according to the description when the research was carried out. The students who were taught by Using Pictorial Poster got better achievement that those who were taught by using conventional technique that was Teacher. the highest score of the pre-test was 65 and the lowest was 45. While the highest score of post-test was 85 and the lowest was 70. The result of means of Pre-Test was 55.33 while the result of deviation standard was 6.32 And the result of means of Post-Test was 78.50. While the result of deviation standard was 5.35 From this research, it was found that the Using Pictorial Poster can cause a positive, which is proven from the result of the test, > or ( 15.44> 2.04 ) there is significance Students Ability in Writing Descriptive Text Skill By Using Pictorial Poster Class VIII Of SMP Negeri 4 Badar In Academic Year 2021/2022.